The Use of Microelectrode Array (MEA) to Study Rat Peritoneal Mast Cell Activation - Chi-Kong Yeung; Jessica Ka-Yan Law; Sze-Wing Sam; Sven Ingebrandt; Hang-Yung Alaster Lau; John Anthony Rudd; Mansun Chan (Elsevier, 2008)
We performed this study to demonstrate the applicability of the microelectrode array (MEA) to study electrophysiological changes of rat peritoneal mast cells in the presence of compound 48/80 under normal, Ca2+-free, Ca2+-free with EDTA, and Cl−-free conditions. The use of high extracellular K+ (KCl, 150 mM), charybdotoxin (ChTX, 100 nM), and Cl−-free containing ChTX buffers verified that the hyperpolarizing signal was due to the activation of mainly K+ and, to a lesser extent, Cl− channels. Compound 48/80 concentration-dependently shortened the latent periods (the onset of response) and increased both the spatial (the K+ and Cl− hyperpolarizing field potentials, HFP) and temporal measurements (the duration of response). Ca2+-free buffer had no effect on the latent period of compound 48/80 but increased the HFP at high concentrations. The latent period increased while the HFP diminished when cells were equilibrated in Ca2+-free buffer containing EDTA. Durations of the HFP were generally longer when cells were in either Ca2+-free or Ca2+-free containing EDTA buffers than when cells were in normal buffer. The EC50 values confirmed that effects were only affected in Ca2+-free buffer containing EDTA but not in Ca2+-free or Cl−-free buffers, further reinforcing the hypothesis that the presence of Ca2+ is not essential to the action of compound 48/80. The present study is the first application of MEA to study rat peritoneal mast cells, and our results indicate that it could be of value in future pharmacological research on other non-excitable cells. Keywords:: rat peritoneal mast cell, hyperpolarizing field potential, potassium channel, calcium channel, microelectrode array